Inga micronectarium (Leguminosae): A new species in the Amazon rainforest, Brazil - Fernandes, José Martins; Soares, Célia Regina Araújo; Silva, Dennis Rodrigues Da (Phytotaxa, 2023)
Inga micronectarium (Leguminosae) is a new species endemic to Brazil and distributed in the states of Mato Grosso and Pará in the Amazon biome. We provide a diagnosis, morphological description, illustration, photograph, and comments about the etymology, flowering and fruiting periods, phytogeography, conservation, and species taxonomy.